Liming of acid soils in Osijek-Baranja county - Dolijanović Željko; Andrijačić Martina; Đurđević Boris; Vukadinović Vladimir; Vukadinović Vesna; Jurišić Mladen; Bertić Blaženka; Jug Irena (Journal of Agricultural Sciences (Belgrade), 2011)
The negative trend of soil degradation process increases with intensive agricultural production. Therefore, there is a need for soil conditioning like liming, humification, fertilization, etc. to improve soil quality. One of the major problems that occur on agricultural soils of Croatia is acidification. A downward trend of soil pH is mainly present in soils of poor structure with intensive agricultural production. In agricultural practice liming often needs to rely only on the pH value, without determining the hydrolytic acidity, CEC or soil texture. Due to the above mentioned facts, calculation of liming for Osijek-Baranja County was conducted with the help of ALRxp calculator, which takes CEC, soil pH in KCl, hydrolytic acidity, bulk density of soil, soil textural class and depth of the plow layer to 30 cm into account. Low soil pH values have a great influence on soil suitability for crops as well as on the deficit of calcium and magnesium. All of these lead to the degradation of soil structure, and can even lead to disturbances of plant nutrition in some production areas. On such soils, liming would be imperatively required, but with caution because an excessive intake of lime materials, especially without the necessary analysis, causes a decline in organic matter and reduces accessibility for plant uptake of microelements.